ANALYSIS OF KALAM INSHA' TOLABI IN THE BOOK "AL-ARBAUN AN-NISAIYYAH" BY MUHAMMAD BIN SYAKIR ASY-SYARIF (BALAGHAH APPROACH) - Fathonatul Ula, Siti; Ghofur, Abdul (Journal of Arabic Language and Literature (ALLAIS), 2024)
This research aims to determine the type of kalam insha' tholabi and reveal its position in the Book of Al-Arba'un An-Nisaiyyah. Kalam insha' tholabi is kalam which wants a demand to happen which has not happened when asked or in belief speaker. The presence of kalam insha tholabi in a sentence shows that there is a certain aim and purpose. To understand it requires an understanding of kalam insha' tholabi so that there are no errors in meaning that cause deviations from the hadith. This research is a descriptive qualitative research using the Milles and Huberman interaction model analysis method with data in the form of words or sentences from hadiths in the book Al-Arba'un An-Nisaiyyah by Muhammad Bin Syakir Asy-Syarif. This research data was collected using the method library research namely by reading and taking notes. This research discovered the types of kalam insha' tholabi and their position after being understood from siyaaqul kalam and qaraainul ahwaal, which is 17 amr, the position: 10 hakiki, and 7 majazi; 9 nahi, the position: 7 hakiki, and 2 majazi; 12 istifham, the position: 8 hakiki, and 4 majazi, 4 tamanni, the position: 4 majazi; 8 nida’, the position: 7 hakiki, and 1 majazi.